Face Recognition Technology for Automatic Attendance System (International Journal of Innovative Research in Computer Science & Technology, 2021)
The attendance system is essential in  schools and colleges. There are several drawbacks to  manual attendance systems, including the fact that they  are less dependable and difficult to maintain. This  enhances accuracy while requiring less time than  previous ways using an attendance system using facial  recognition technology. There are several current  attendance systems, such as IoT facial detection, PIR, and  so on. For facial recognition, hardware devices are also  helpful. The problem is to ensure that all sensors function  well without damage. The aim is to use the hair cascade  algorithm to create a system with the best accuracy of all  of the methods and methods. Images may be taken  between 50 and 70 cm away. A graphical user interface is  meant to let users with one click to collect images, build  datasets and train datasets. After recognition of the face,  it shows the student's name and roll number. In the  attendance sheet, the information is automatically  provided together with the date and time.
Keywords: face detection; face recognition; Haar features; histogram of oriented gradient; PIR sensor